Downscaling approach to evaluate future climate change impacts on urban hydrology - Herath, Mudiyanselage Sujeewa Malwila Herath (Curtin University, 2017)
This research introduces an approach to develop IDF relations under the context of climate change. SDSM tool is used for spatial downscaling and GEV distribution is used for temporal downscaling of GCM data. Also an empirical relationship between the extreme rainfalls and daily maximum temperature is evaluated. Developed IDF relations are used for hydrological modelling to evaluate the combined impacts of climate change and land use change on the urban catchments and urban stormwater management.